Influence of Plant Growth Regulators on Growth, Flowering and Quality of Tomato (Lycopersicon Esculentum Mill), cv. H-86 - SINGH VERMA, PRAWAL PRATAP; MEENA, M. L.; MEENA, SURESH KUMAR (Indian Journal of Hill Farming, 2015)
The experiment was laid out in randomized block design with three replication at Horticulture Research Farm, under DAPS (Horticulture), BBAU Lucknow, during rabi season 2011 to 2012 with the objectives to study the effect of varying levels of NAA, 2, 4-D and GA3 on growth, quality and yield of tomato and to ascertain the best concentration of NAA, 2, 4-D and GA3 for vegetative growth and fruit quality of tomato. The experiment consisted one tomato variety viz .kashi vishesh (H-86) and different levels of NAA (15, 30, 45 ppm), 2, 4-D (5, 10, 15 ppm) and GA3 (20, 30, 40 ppm) of different concentrations were used. The result showed maximum yield per hectare. These results are of my own study and are unique and can be very useful in research from trial to field, so it will be of interest to implement these results to the field to harvest good yield of tomato.